2020
DOI: 10.2495/hpsm200131
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nanofiber Loading and Moulding Conditions on the Joining Strength of Thermoplastic Composites Fabricated by Injection Over-Moulding Process

Abstract: An over-moulding process has promised a novel technology for joining lightweight thermoplastic composites with metal or polymer composite parts. Specifically, the substrate parts (metal or textile composites) are put into a mould of the injection moulding machine and melt polymer is injected onto substrate parts. This over-moulding process provides great benefits in terms of fast welding and moulding at the same time. However, the interfacial joining strength of over-moulded parts is still unreliable, and it h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In the influence of the CNF content, the addition of 1.0 wt% CNF to the PP nanocomposite film increased the joining strength under all process conditions. Furthermore, the addition of 2.0 wt% CNF deteriorated the lap shear strength compared with the 1.0 wt% CNF-filled single lap joint, as reported in our previous work [13], [14]. Thus, these results showed that the optimum content of CNFs existed.…”
Section: Influence Of Molding Conditions and Cnf Content On The Joini...supporting
confidence: 81%
See 3 more Smart Citations
“…In the influence of the CNF content, the addition of 1.0 wt% CNF to the PP nanocomposite film increased the joining strength under all process conditions. Furthermore, the addition of 2.0 wt% CNF deteriorated the lap shear strength compared with the 1.0 wt% CNF-filled single lap joint, as reported in our previous work [13], [14]. Thus, these results showed that the optimum content of CNFs existed.…”
Section: Influence Of Molding Conditions and Cnf Content On The Joini...supporting
confidence: 81%
“…The details of the fabrication process of a single lap joint reinforced by CNFs at the joining area are described in the literature [14]. The fabrication processes are divided into two steps: (A) fabrication of CFRTP laminate and (B) overmolding of PP onto the CFRTP substrate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations